المدخل إلى دراسة علوم القرآن An introduction to the study of the sciences of the Noble Quran - Samsudin, Sofiah (IIUM Press, 2025)
This book presents a simplified overview of ʿUlūm al-Qurʾān (Qur'anic sciences), one of the most esteemed and essential fields in Islamic studies. It summarizes classical and contemporary scholarship in this discipline, using accessible language supported by tables and illustrations to help convey key concepts—especially for beginners and non-Arabic speakers. The book covers twenty major topics, beginning with the Muslim’s duty toward the Qur'an, followed by key subjects such as its revelation, compilation, and arrangement, and ending with contemporary issues such as Qur'an translation and interpretation. Designed to align with university curricula—particularly that of the International Islamic University Malaysia (IIUM)—this book serves as a valuable reference for students and researchers in Qur'anic studies.